Nationalisation and Reprivatisation of Forests in Poland after World War II - Jaroszyk, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article concerns the transfer of ownership of forest property, nationalized after World War II. It covers the process of property acquisition by way of nationalization decrees and dilemmas related to the issue of reprivatisation. Nationalization of forests throughout the country was mainly based on the Decree of the PKWN of December 12, 1944. on the takeover of some forests under the ownership of the Treasury. This decree was a supplement to the decree on agricultural reform, which initiated changes in the system and ownership after the Second World War. In a sense, it crowned the ‘task’ of nationalization, covering forests with a smaller area, not subject to the takeover under the agricultural reform decree. Different legal grounds for the nationalization of forests determined different re-privatization procedures initiated after 1989. The work includes issues proposed over the years and existing statutory solutions, as well as case law affecting the interpretation of legal norms.

Artykuł dotyczy problematyki przeniesienia własności nieruchomości leśnych znacjonalizowanych po II wojnie światowej. Obejmuje tematykę nabywania majątku w drodze dekretów nacjonalizacyjnych oraz dylematy związane z kwestią reprywatyzacji. Nacjonalizacja lasów w całym kraju odbywała się głównie na podstawie dekretu PKWN z dnia 12 grudnia 1944 r. o przejęciu niektórych lasów na własność Skarbu Państwa. Dekret ten był uzupełnieniem dekretu o reformie rolnej, który zapoczątkował zmiany ustrojowe i właścicielskie po II wojnie światowej. W pewnym sensie ukoronował dzieło nacjonalizacji, obejmując lasy o mniejszej powierzchni, niepodlegające przejęciu na mocy dekretu o reformie rolnej. Różne podstawy prawne nacjonalizacji lasów determinowały procedury reprywatyzacyjne wszczęte po 1989 r. W artykule uwzględniono inicjatywy legislacyjne podejmowane na przestrzeni lat oraz istniejące rozwiązania ustawowe, a także orzecznictwo wpływające na wykładnię norm prawnych.
Keywords: transfer of ownership; nationalization; reprivatisation; forests; transfer własności; nacjonalizacja; reprywatyzacja; lasy